2021
DOI: 10.1007/s13340-021-00497-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the quality of diabetes care in Japan: a systematic review of the literature

Abstract: Background Among chronic diseases, diabetes is a frequent focus of performance measurement. Disease-specific indicators based on evidence-based clinical guidelines have been used to evaluate the quality of care. There are worldwide efforts to improve the quality of diabetes care. Measuring the gap is an essential first step toward improving the quality of care. Methods In order to better understand the status of quality of diabetes care in Japan, a country with a universal healthcare system, we performed a lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study showed low implementation rates for quantitative urine albumin and protein testing as DKD screening, which are recommended in the guidelines ( 7 , 8 ). Although urine screening testing is recommended every 3 to 6 months and is covered by health insurance in Japan, the actual frequency of testing is lower than recommended ( 23 , 25 , 26 ). The actual frequency of urine screening testing in Japan is lower than that in other developed countries ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed low implementation rates for quantitative urine albumin and protein testing as DKD screening, which are recommended in the guidelines ( 7 , 8 ). Although urine screening testing is recommended every 3 to 6 months and is covered by health insurance in Japan, the actual frequency of testing is lower than recommended ( 23 , 25 , 26 ). The actual frequency of urine screening testing in Japan is lower than that in other developed countries ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 2 diabetes in Japan visit the hospital once every month or every few months to measurement of the HbA1c level [ 12 , 13 ]. More frequent testing of HbA1c has been reported as not being effective in improving the glycemia status [ 14 ] because of the relatively long half-life of hemoglobin.…”
Section: Introductionmentioning
confidence: 99%